2016
DOI: 10.1103/physrevlett.117.076101
|View full text |Cite
|
Sign up to set email alerts
|

Chromatic Aberration Correction for Atomic Resolution TEM Imaging from 20 to 80 kV

Abstract: Atomic resolution in transmission electron microscopy of thin and light-atom materials requires a rigorous reduction of the beam energy to reduce knockon damage. However, at the same time, the chromatic aberration deteriorates the resolution of the TEM image dramatically. Within the framework of the SALVE project, we introduce a newly developed C_{c}/C_{s} corrector that is capable of correcting both the chromatic and the spherical aberration in the range of accelerating voltages from 20 to 80 kV. The correcto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(98 citation statements)
references
References 30 publications
2
96
0
Order By: Relevance
“…For the confidence intervals we took √ N for N, √ V for V, and 1% for the electron dose were assumed. The values for the damage-cross-section of MoS2 were taken from 15 (4) 0.008 (3) of the total damage production. Taking into account that 24% of the damage is produced by knock-on damage, 63% by heat, charge and/or electronic excitations, then 13% of the damage has to be produced by other mechanisms, such as chemical etching and further ionization effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the confidence intervals we took √ N for N, √ V for V, and 1% for the electron dose were assumed. The values for the damage-cross-section of MoS2 were taken from 15 (4) 0.008 (3) of the total damage production. Taking into account that 24% of the damage is produced by knock-on damage, 63% by heat, charge and/or electronic excitations, then 13% of the damage has to be produced by other mechanisms, such as chemical etching and further ionization effects.…”
Section: Resultsmentioning
confidence: 99%
“…Modern transmission electron microscopes (TEM) allow imaging materials at a single atom resolution with acceleration voltages in the range of 20-300 kV [1][2][3] , foremost thanks to the practical realization of aberration correctors (AC) for transmission electron microscopy 4,5 . However, high electron doses are required for achieving a high enough signal to noise ratio for accurate detection of the atom position in the image.…”
Section: Introductionmentioning
confidence: 99%
“…For a round lens, the paraxial ray trajectory r(z) derived from equations (3) can be reduced to the equation (6). In equation (6), η is the charge to mass ratio.…”
Section: The Design Of Compact C S Correctormentioning
confidence: 99%
“…In the past decade, it has been demonstrated that the aberration-corrected scanning transmission electron microscopes (STEM) reaches sub-angstrom resolution [1] with sensitivity that is sufficient to detect even single light atoms [2]. The success of the aberration corrector motivates the development trend toward low voltage electron microscope (LVEM) for radiation sensitive materials, while maintaining high resolution [3][4][5][6]. The desktop STEM without aberration corrector operated at low voltage is available in the recent years [7].…”
Section: Introductionmentioning
confidence: 99%
“…Hardware aberration correction for electron beams in transmission electron microscopy (TEM) is now widespread, substantially improving the interpretable resolution in TEM micrographs [14]. This technology is enabled by the combination of two factors; the ability to accurately measure optical aberrations in the electron beam, and a system of multipole lenses that can compensate for these measured aberrations.…”
Section: Introductionmentioning
confidence: 99%